2012
DOI: 10.1177/1076029611427438
|View full text |Cite
|
Sign up to set email alerts
|

Skin Bleeding Time for the Evaluation of Uremic Platelet Dysfunction and Effect of Dialysis

Abstract: Skin bleeding time could reveal the uremic platelet dysfunction and beneficial effect of dialysis in the patients who presented with uremic symptoms and treated with HD for the first time. We suggest that skin bleeding time may be an appropriate test for the evaluation of hemostasis disturbance in uremic patients and prediction of the bleeding risk before invasive procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
9
0
3
Order By: Relevance
“…Soyoral et al reported that skin bleeding-time after the first HD was shorter compared to the pre-dialysis value, because HD improves uremia and platelet function 21 . Winkelmayer et al reported that CKD was associated with the risk for postoperative bleeding in patients undergoing coronary artery bypass grafting surgery, not only at more advanced stages, but probably also at relatively mild levels of renal impairment 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Soyoral et al reported that skin bleeding-time after the first HD was shorter compared to the pre-dialysis value, because HD improves uremia and platelet function 21 . Winkelmayer et al reported that CKD was associated with the risk for postoperative bleeding in patients undergoing coronary artery bypass grafting surgery, not only at more advanced stages, but probably also at relatively mild levels of renal impairment 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Altman et al [16] reported the correlation between results of template BT and degree of platelet inhibition as well as bleeding episodes in patients who were under aspirin and clopidogrel treatment. About evaluation of bleeding in patients with renal failure, previous data found that BT was a useful test to evaluate bleeding risk in uremic patients [17,18]. Another preanalytical issue of BT is the setting of rejection criteria for patients with anemia and/or thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the in vivo bleeding time according to the template or Ivy bleeding time test has been shown to reflect global hemostatic defects in uremia in smaller studies. 103 Under standardized conditions with a sphygmomanometer at the forearm inflated to 40 mm Hg, to control the venous pressure, two standardized incisions are made at the volar Fig. 3 Effect of hemodialysis on platelets.…”
Section: Skin Bleeding Timementioning
confidence: 99%
“…An analysis of patients after the initiation of dialysis revealed that the skin bleeding time was significantly reduced with regular dialysis. 103 However, due to questionable accuracy and reproducibility, this test is obsolete.…”
Section: Skin Bleeding Timementioning
confidence: 99%